Kuat Tekan Beton Geopolimer Dengan Variasi Berat Agregat Dan Binder Pada Umur Beton 21 dan 28 Hari - Yunanto, Andi; , Ir. Suhendro Trinugroho, M.T (2017)
Concrete is a building material that is composed of the main composition of coarse aggregate, fine aggregate, water, and Portland Cement. Concrete lately more often get criticism, because of greenhouse gas emissions (carbon dioxide) generated in the cement production process. With these considerations, the development of new concrete binder called geopolymer concrete. One of the materials used in the manufacture of geopolymer concrete is coal fly ash (fly ash). By making use of fly ash as a substitute ingredient of cement is considered to safeguard the environment and reduce the cost of construction. In this study, the test object used is cylindrical, with a diameter of 15cm and height 30cm. Tests carried out at the time of compressive strength of concrete were 21 and 28 days. The present study aims to determine the compressive strength of geopolymer concrete with maximum possible variation of constituent materials, aggregate with a binder that is 75:25, 30:70, 35:65 and 40:60 and the variation of the concrete 21, 28 days. Mix design refers to earlier research Prasetyo, G.B (2015). Number of test objects on each variation is 3 specimens, so that the number of test objects totaling 24 pieces. The test object is a cylinder with a diameter of 15cm and height 30cm. Data from geopolymer concrete compressive strength test on the variation ratio of 25:75 and the constituents of the concrete age variation of 21 days was 0.314 MPa, and at 28 days is 0720 MPa. At 30:70 constituent material ratio variation and the variation of the concrete life of 21 days was 1,491 MPa, and at 28 days was 2,055 MPa. At 35:65 constituent material ratio variation and the variation of the concrete life of 21 days was 1,807 MPa, and at 28 days was 2,192 MPa. At 40:60 constituent material ratio variation and the variation of the concrete life of 21 days is 0854 MPa, and at 28 days was 1.699 MPa. It can be concluded that the variations of geopolymer concrete building blocks the maximum at 35:65 ratio at 28 days.